2019
DOI: 10.3390/agronomy9120845
|View full text |Cite
|
Sign up to set email alerts
|

Conservation Agriculture Improves Long-term Yield and Soil Quality in Irrigated Maize-oats Rotation

Abstract: Conservation agriculture, characterized by minimal tillage, permanent soil cover and crop diversification, has been widely adapted under rainfed conditions, but adoption under irrigated conditions is limited. An experiment initiated in 1997 to evaluate the level of tillage and the amount of soil cover needed for conservation agriculture to work under irrigated conditions in the highlands of San Luis Potosí, Mexico. The trial encompassed seven treatments: conventional tillage, two types of reduced tillage and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…The higher EC under CA (Figure 4b) was probably caused by this accumulation of nutrients in the 0–5 cm layer. Higher concentrations of nutrients such as N (Grahmann et al, 2020), P (Fonteyne et al, 2019), and K (Singh et al, 2018) have been reported in other studies, but it is still unclear how residue retention impacts soil nutrient cycles and fertilization requirements. A review in Africa showed CA required supplemental N fertilization to correct for N immobilization by residues (Thierfelder et al, 2018), although other studies have shown that subsurface fertilizer application can reduce N immobilization under CA (Grahmann, Verhulst, Buerkert, Ortiz‐Monasterio, & Govaerts, 2013).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…The higher EC under CA (Figure 4b) was probably caused by this accumulation of nutrients in the 0–5 cm layer. Higher concentrations of nutrients such as N (Grahmann et al, 2020), P (Fonteyne et al, 2019), and K (Singh et al, 2018) have been reported in other studies, but it is still unclear how residue retention impacts soil nutrient cycles and fertilization requirements. A review in Africa showed CA required supplemental N fertilization to correct for N immobilization by residues (Thierfelder et al, 2018), although other studies have shown that subsurface fertilizer application can reduce N immobilization under CA (Grahmann, Verhulst, Buerkert, Ortiz‐Monasterio, & Govaerts, 2013).…”
Section: Discussionmentioning
confidence: 90%
“…At Texcoco I, soil health has been studied extensively and, compared to conventional tillage, soils under CA have higher infiltration rates, maintained higher moisture contents throughout the growing season, and gave higher yields (Verhulst et al, 2011). At Soledad de Graciano Sánchez, the infiltration rate was considerably higher under CA, improving irrigation efficiency and raising maize yields (Fonteyne et al, 2019). Measurements were made on top of permanent raised beds or close to the sowing line in flat planting, to foster comparability between samples and because this is the most relevant zone for plant growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Crop residues left over the soil in CA provide protection from raindrop impact, reduce flow of surface runoff and may prevent pore sealing and crust formation, increasing the available water to be infiltrate and reducing evapotranspiration [99]. In this line, although some authors suggest that CA may allow for saving irrigation water by improving soil water retention properties (and reducing evapotranspiration) [100,101], no differences on AWHC were observed within groups where this strategy was applied in irrigated conditions (Figure 11).…”
Section: Adaptive Management and Available Water-holding Capacitymentioning
confidence: 99%
“…The observed variability in terms of the adoption and effectiveness of the five strategies tested in this region also suggests that one strategy alone might be not enough to globally improve the soil physical condition. In this sense, some authors have proposed the combination of measures such as irrigation [101,111] with cover crops and/or animal manure application [82], as more effective for instance to improve the potential of no-till in order to enhance the physical properties of the soil and guarantee profitable yields [112]. Priori et al [89] also proposed a combination of cover crops with the use of proper organic amendments, subsoiling techniques as well as use of biological inoculants in degraded areas of tree crops, in order to couple their positive effect.…”
Section: Regional Assessmentmentioning
confidence: 99%